2017
DOI: 10.1038/s41467-017-01014-4
|View full text |Cite
|
Sign up to set email alerts
|

A sexually dimorphic pre-stressed translational signature in CA3 pyramidal neurons of BDNF Val66Met mice

Abstract: Males and females use distinct brain circuits to cope with similar challenges. Using RNA sequencing of ribosome-bound mRNA from hippocampal CA3 neurons, we found remarkable sex differences and discovered that female mice displayed greater gene expression activation after acute stress than males. Stress-sensitive BDNF Val66Met mice of both sexes show a pre-stressed translational phenotype in which the same genes that are activated without applied stress are also induced in wild-type mice by an acute stressor. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 72 publications
12
57
0
Order By: Relevance
“…Given that male and female mice used in this study were generated in separate cohorts (see Methods), experienced different adult stresses (STVS or repeated social defeat), and tissue was processed separately, we have deliberately avoided direct comparisons of potential sex differences in response to stress as sex and cohort variables cannot be distinguished. RNAseq in both human and mouse brain reveals substantial sex differences at baseline as well as in human depression and stressed mice 13,[46][47][48] . Nevertheless, it is still useful to consider here similarities in biological pathways affected by each stress or combination of stresses among male and female mice, even when distinct genes contribute to pathway enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Given that male and female mice used in this study were generated in separate cohorts (see Methods), experienced different adult stresses (STVS or repeated social defeat), and tissue was processed separately, we have deliberately avoided direct comparisons of potential sex differences in response to stress as sex and cohort variables cannot be distinguished. RNAseq in both human and mouse brain reveals substantial sex differences at baseline as well as in human depression and stressed mice 13,[46][47][48] . Nevertheless, it is still useful to consider here similarities in biological pathways affected by each stress or combination of stresses among male and female mice, even when distinct genes contribute to pathway enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies, using RNA‐sequencing on translating ribosome affinity purified (TRAP) pyramidal neurons of the hippocampus CA3, recently explored the actively translated immediate early genes in response to an acute forced swim test . The authors found that while both males and females showed many DEGs (including the expected cFos and Arc ), female DEGs were found to be almost three times more in number than the ones found in males.…”
Section: Rodent Studiesmentioning
confidence: 99%
“…Curiously, the majority of genes were expressed similarly in OVX WT treated with E2 and vehicle-treated OVX Het-Met mice. This was reminiscent of the "pre-stressed state" of Het-Met mice where the same genes that are expressed without applied stress are also induced in WT mice by an acute stressor [6]. Only a minority of genes (a cluster of 43 genes and a cluster of 30 genes) was regulated similarly by E2 in both OVX WT and OVX Het-Met mice (Fig.…”
Section: Sequencing Analysis and Statisticsmentioning
confidence: 90%
“…Raw reads were trimmed, filtered, and aligned to mouse genome (mm10) using TopHat2 [6]. Differential expression analysis (average of three samples per group) was conducted with Strand NGS software (Agilent Technologies, USA), in which DESeq was used to quantify transcript reads and obtain z-scores and fold change values for individual genes.…”
Section: Sequencing Analysis and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation